Does pre-fellowship experience alter success rates of endoscopic treatment of vesicoureteral reflux during pediatric urology fellowship?. Issue 4 (August 2022) - Selvi, Ismail; Canbaz, Furkan Adem; Dönmez, M. İrfan; Özkuvancı, Ünsal; Çetin, Bilal; Kart, Mücahit; Oktar, Tayfun; Ziylan, Orhan
Summary: Introduction: Learning curve is a well-known factor that affects the success rate of endoscopic injection for vesicoureteral reflux (VUR). Objective: To our knowledge, the significance of pre-fellowship training has not been studied. In the present study, our aim was to investigate the effect of pre-fellowship training on the endoscopic treatment success rates of pediatric urology fellows. Design: A total of 78 patients aged 2–16 years (132 renal units) who underwent subureteric injection for the treatment of primary VUR by four pediatric urology fellows between 2014 and 2020 were retrospectively evaluated. Fellows were grouped into two as experienced and non-experienced according to the presence of pre-fellowship experience (defined as a minimum of 20 procedures). Patients in both groups were divided into two subgroups as non-dilating (grade I-II) and dilating VUR (grade III-V). Also, the change in success rate throughout the fellowship was analyzed. HIT or Double HIT method was used in all interventions. Results: Experienced fellows carried out subureteric injection in 54 (40.9%) renal units while non-experienced fellows performed in 78 (59.1%). There was no success rate difference between experienced and non-experienced fellow groups in non-dilating VUR (100% vs. 88%, respectively p = 0.268), whereas the success rate of the experienced group was significantly higher in dilated VUR (78.9% vs. 50.9%, p = 0.006). Moreover, the amount of material used in the treatment of non-dilating VUR were similar between two fellow groups (0.6 ml vs. 0.6 ml, p = 0.500), while experienced group achieved higher success rates in dilating VUR by statistically significant less amount of injected volume (0.7 ml vs. 0.9 ml, p = 0.026).Overall complete VUR resolution rates were similar throughout the fellowship period in the experienced fellows (81.5% vs. 88.9%, p = 0.444), while it significantly increased in the non-experienced group implicating the completion of the learning curve (51.3% vs. 74.4%, p = 0.035). Discussion: There has been no published reports on the effect of pre-fellowship experience on subureteric injection success. While many researchers reported on the importance of learning curve, various studies assessed the effect of injected volume on success rate implicating contradictory results. Furthermore, others indicated that the ideal technique providing accurate needle placement and obtaining proper depth during injection which is associated with surgical experience is more important than the injected volume in achieving success. Conclusion: Our results implicate that similar success rates in non-dilating VUR can be achieved regardless of previous subureteric injection training. However, higher failure rates may be expected when the procedures are performed by non-experienced pediatric urology fellows at the beginning of their fellowship in dilating VUR. Summary figure The graph shows the change of overall complete VUR resolution rates in four fellows, individually, by case number. Summary figure